Landscape Planning and Residential Growth in a Water Source Area in Presidente Prudente-SP - Sandeville Junior, Euler; Silva, Matheus Morais Gonçalves da; Araujo, André Aparecido da Silva; Moreno, Diego Delmore; Moreno, Diego Delmore; Damaceno, Ian; Santos, Lucia Ramalho Ferreira dos (National Journal of City Management, 2025)
Objective – Through the analysis of land use in the Cedro sub-basin, within the Alto Anastácio Basin, Presidente Prudente, SP —an essential water source for the urban supply of Presidente Prudente—and in the Ana Jacinta Housing Complex, this study aims to demonstrate how landscape planning and management can serve as powerful tools for territorial understanding. By providing a comprehensive perspective on these dynamics, the study supports the formulation of more sensitive public policies for areas experiencing peripheral urban growth. Methodology – This article is the result of the following procedures: in-person theoretical classes on landscape planning, using analysis and discussion of bibliographic references, the legal framework of the Master Plan compared with the dynamics of ongoing urban expansion vectors in a water source area, along with cartographic analyses of the study area using QGIS software. This is followed by a field study in the analyzed area, aiming to listen to residents to understand their emotional valuation of the place and the problems they face. Finally, all data is systematized to propose a series of reflections, identifying conflicts and highlighting the urgency of more sensitive practices regarding the studied landscape as a basis for revising the legal planning framework and the need for decentralized managemente. Originality/Relevance – There has been a growing discussion on the urgency of landscape planning and management in urban planning processes and public administration, especially in peripheral areas and those undergoing recent urban expansion. This study seeks, through a shared analysis, to integrate cartographic and fieldwork methods along with residents’ perspectives as essential for interpreting the landscape, aiming at its diagnosis and planning. Results – The study fosters a critical discussion on the aspects involved in a landscape regulation and management plan, generating cartographic products and a series of reflections that can support public policies by the agents and institutions responsible for implementing territorial planning. These entities could recognize the potential of an integrated approach to landscape analysis. Theoretical/Methodological Contributions – The text provides a methodological approach to support the development of future propositions, based on a knowledge-building process shared by researchers from various fields (architects, educators, environmental engineers, and archivists). It aims to demonstrate that the multiplicity of perspectives enriches discussions, proving that initiatives following this approach result in more sensitive outcomes, especially regarding landscape studies. Social and Environmental Contributions - Investigating an area that clearly expresses socio-spatial fragmentation— a process currently unfolding in many Brazilian cities—and proposing a critical stance that considers the physical, environmental, and social aspects of the place is a fundamental exercise for the development of public policies that protect the environment and improve people’s quality of life, especially for those living in the most remote areas of urban centers.